2006
DOI: 10.1099/jmm.0.46550-0
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococci causing invasive disease in children prior to the introduction of pneumococcal conjugate vaccine in Scotland

Abstract: This study aimed to determine the serotypes and sequence types (STs) of pneumococci causing paediatric invasive disease in Scotland prior to the introduction of pneumococcal conjugate vaccines (PCVs). All invasive pneumococci isolated between 2000 and 2004 from children aged less than 5 years in Scotland were used. The isolates were characterized by serotyping and multi-locus sequence typing. Two hundred and seventeen pneumococci were characterized into 22 different serogroups/types, the most common, in rank o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…16 – 20 , 23 When compared globally to those observed in Latin America, North America, and Europe, the 10 prevalent serotypes prior to 2010 in the present study were comparably well represented in samples from elsewhere in the pre-PCV7 and early post-PCV7 eras. 2 , 5 , 6 , 9 , 22 , 26 , 33 37 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 – 20 , 23 When compared globally to those observed in Latin America, North America, and Europe, the 10 prevalent serotypes prior to 2010 in the present study were comparably well represented in samples from elsewhere in the pre-PCV7 and early post-PCV7 eras. 2 , 5 , 6 , 9 , 22 , 26 , 33 37 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, serotype 14 was represented by four STs in the USA and 12 STs in Scotland during the pre-PCV era, and quite striking was the absence of ST156 in Scotland. 33 , 37 , 39 ST156 has frequently occurred worldwide and was first described as serotype 9V; this has subsequently also been described as serotype 14 and as other serotypes. 25 , 57 Furthermore, ST156 is often associated with antibiotic resistance and is one of the well described PMEN clones (Spain 9V -ST156, PMEN3) that have spread globally, including within the Latin America region.…”
Section: Discussionmentioning
confidence: 99%
“…The most striking example of this was for serotype 14, for which we observed 15 different STs (Table 2). In a UK study carried out in Scotland, serotype 14 was the most common serotype isolated from paediatric IPD prior to PCV7 introduction (Clarke et al, 2006;Jefferies et al, 2010) and was represented by 12 STs of which ST9 and ST124 were by far the most common. In the present study, ST9 was also the most common (n511).…”
Section: Serotype/genotype Relationshipsmentioning
confidence: 99%
“…The predominant serotypes observed in the present study comprised genetically diverse clones as demonstrated by previous studies in the United Kingdom [14,15]. Within a single serotype, genetic variability may have arisen largely by divergence from ancestral clones through evolutionary biology.…”
Section: Resultsmentioning
confidence: 71%